Mechanochemical synthesis and characterisation of BaTa2O6 ceramic powders - Ilhan, Mustafa; Mergen, Ayhan; Yaman, Cemalettin (ELSEVIER SCI LTD, 2011)
Mechanochemical synthesis was used to prepare BaTa2O6 powders from BaCO3 and Ta2O5 precursors in a planetary ball mill. Effect of milling time and heat treatment temperature on the formation of BaTa2O6 and on the microstructure was investigated. Intensive milling of starting materials resulted in crystallization of BaTa2O6 even after 1 h of milling time and single phase BaTa2O6 was obtained after 10 h of milling under optimal conditions. The powder derived from 10 h of mechanical activation had crystallite size of 22 nm. But the increase in milling time did not decrease the crystallite size further. High energy milling activated the powders that although 1 h of milling led to formation of single phase BaTa2O6 at 1200 degrees C, this temperature decreased to 900 degrees C after 5 h of milling. No significant grain growth was observed when the milled powders were heat treated below 900 degrees C. However, annealing at 1100 and 1200 degrees C gave an average BaTa2O6 grain size of 180 and 650 nm, respectively. An unidentified phase started to form at 1100 degrees C increasing to high amounts at 1200 degrees C and they had different shapes and sizes than BaTa2O6 grains. These elongated large grains were thought to be due to liquid phase formation caused by iron contamination. (C) 2011 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: X-ray method; BaTa2O6; Mechanosynthesis; MICROWAVE DIELECTRIC-PROPERTIES; H-2; Materials Science